Rosemary's baby [videorecording (DVD)] - Polanski, Roman; Farrow, Mia, 1945-; Cassavetes, John, 1929-1989; Gordon, Ruth, 1896-1985; Levin, Ira, 1929-2007 (Paramount Pictures, 2000)
After unwittingly becoming friendly with a coven of witches and warlocks, a young wife is impregnated by the Devil.